A Square Wave Voltammetry Study on the Antioxidant Interaction and Effect of Extraction Method for Binary Fruit Mixture Extracts - Claudia Giovagnoli-Vicuña; Sebastián Pizarro; Vilbett Briones-Labarca; Álvaro Delgadillo (Journal of Chemistry)
Square wave voltammetry (SWV) analysis was used to assess the antioxidant interactions (synergism, addition, and antagonism) of fruit mixture extracts from grape (G), lemon (L), and blueberry (B) obtained by conventional extraction, ultrasound-assisted extraction, and high hydrostatic pressure extraction. The experimental results showed antagonistic antioxidant effects in all binary mixture extracts (L-G, L-B, and G-B). In DPPH and FRAP assays, the greatest antioxidant capacity was found in the G-B mixture (108.7 and 108.8 μmol TE g−1 dry extract, respectively) obtained by high hydrostatic pressure extraction; however, there were no significant differences when measured by ultrasound-assisted extraction. For TPC and TFC assays, the greatest values were for G-B (6.67 mg GA g−1 dry extract) and L-G (1.63 mg QE g−1 dry extract), respectively. SWV experiments showed antagonistic behavior in the mixtures. Among the different ratios of the fruit mixture extracts evaluated by SWV, 1 : 1 (w/w) combination showed the greatest antagonistic antioxidant effects. SWV suggests the components of the mixture with the highest antioxidant capacity oxidize after mixing. The results indicate that the presence of natural bioactive antioxidants in fruit mixtures does not guarantee that the interactions are synergistic.